Pengaruh Inflasi, Kurs, BI Rate terhadap Jumlah Tabungan Mudharabah pada Bank Umum Syariah Periode 2016-2020 - Moh Al Farisi; Tajus Subqi (Alkasb: Journal of Islamic Economics, 2023)
Inflation and BI Rate are macroeconomic factors that can affect mudharabah savings. Inflation is considered a source of decreased purchasing power that occurs because the amount of money in circulation is too large, so to counteract it must reduce the amount of money in circulation. Reducing the amount of money in circulation will lead to high interest rates (BI Rate). The high prices and incomes that remain or increase according to the magnitude of inflation make people have no excess funds to be stored in the form of savings. The high interest of customers to save is influenced by the interest rate (BI Rate), another factor that affects mudharabah savings is the exchange rate of the rupiah against the dollar (exchange rate), the exchange between different currency values results in a comparison of values or prices between the two currencies. Thus, researchers aim to test and analyze the effect of inflation, exchange rates, BI Rate on the amount of mudharabah savings at Islamic Commercial Banks for the 2016-2020 period. This study uses secondary data in the form of annual data from 2016-2020 using multiple linear regression analysis tools. The sample technique used in this study was purposive sampling, with a total sample of 35 consisting of 7 banks listed in Islamic Commercial Banks. This research uses the Eviews version 12 and Microsoft Excel 2019 applications. The results showed that the exchange rate and BI Rate partially had a significant effect on the amount of mudharabah savings. While inflation partially has no significant effect on the amount of mudharabah savings. Simultaneously inflation, exchange rate, and BI Rate have a significant effect on the amount of mudharabah savings.